Morphology Modulation in Self-Assembly of Chiral 2-Hydroxy-2-Phenylacetic Acids in Polymeric Diluents - Baiq Firyal Salsabila Safitri; Eamor M. Woo (Crystals, 2022)
This study focused on the chirality effects that control the lamellar bending sense in self-assembled crystals of chiral 2-hydroxy-2-phenylacetic acids. 2-Hydroxy-2-phenylacetic acid or mandelic acid (MA) was crystallized in the presence of poly(4-vinyl phenol) (PVPh), and its crystalline structures and morphologies were assessed using polarized optical microscopy (POM) and scanning electron microscopy (SEM). MA of two opposite chiral forms (S- and R-) was crystallized with PVPh as the morphology modulator; with adjustment of the PVPh content, the morphology of MA crystals transforms from ring-banded spherulites to highly dendritic spherulites. For MA/PVPh (50/50 wt./wt.) blend and neat MA at same Tc, the dendritic spherulites are packed with single crystals where the lamellae bend at a specific direction varying with Tc and chirality. Contrary to conventional thought, the bending senses of the MA lamellae in the dendritic spherulites are not solely governed by the MA molecular chirality (S or R), but also by Tc. Only at high Tc (>65 °C) is the lamellar bending direction in dendritic spherulites of (S)-MA or (R)-MA blended with PVPh dictated by the chirality, i.e., displaying counterclockwise and clockwise bending direction for (S)-MA/PVPh and (R)-MA/PVPh, respectively. Nevertheless, at low Tc (45 °C), the bending sense of dendritic spherulites displays an opposite direction from those at the higher Tc, which is to say that the chirality alone does not control the lamellar bending direction.